2017
DOI: 10.17511/ijphr.2017.i1.02
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding mosquito borne diseases & control measures practiced among a rural population in a southern district of Tamil Nadu, South India

Abstract: Introduction:Vector-borne diseases account for over 17% of all infectious diseases. Up to 700 million people are infected and more than a million die each year from mosquito-borne illness. The extent of people's cooperation can determine the success or failure of the entire campaign for Mosquito control. Methods: A cross-sectional observational study was carried out in Kanyakumari district among 180 individuals selected through multi-stage sampling. Data was collected using a semi structured interview schedule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Global literature supported the magnitude of assessment of awareness programme on malaria that used conventional pre–post cognitive educational approaches. [131415161718192021222324] However, recent study from Ghana reported role of empowering the teachers for primordial prevention among school students for good understanding of malaria and its vectors. [25] Our observations that the key activity of enhancing knowledge of the downtrodden tribal people and empowering their community should be the mainstay to overpower the menace of malaria were supported in recent literatures also.…”
Section: Discussionmentioning
confidence: 99%
“…Global literature supported the magnitude of assessment of awareness programme on malaria that used conventional pre–post cognitive educational approaches. [131415161718192021222324] However, recent study from Ghana reported role of empowering the teachers for primordial prevention among school students for good understanding of malaria and its vectors. [25] Our observations that the key activity of enhancing knowledge of the downtrodden tribal people and empowering their community should be the mainstay to overpower the menace of malaria were supported in recent literatures also.…”
Section: Discussionmentioning
confidence: 99%
“…Among various carriers of disease causing pathogens, insects plays major role. Among various diseases caused in humans, 17 % infections are through vectors (Ben Nelson S, et al, 2017). Insects including mosquito, tick, lice, housefly, sandfly, etc.…”
Section: Introductionmentioning
confidence: 99%